How Times of Crisis Serve as a Catalyst for Creative Action: An Agentic Perspective - Beghetto, Ronald A. (Frontiers in Psychology, 2021)
The human experience is punctuated by times of crisis. Some crises are experienced at a personal level (e.g., the diagnosis of a life-threatening disease), organizational level (e.g., a business facing bankruptcy), and still others are experienced on a societal or global level (e.g., COVID-19 pandemic). Although crises can be deeply troubling and anxiety provoking, they can also serve as an important catalyst for creative action and innovative outcomes. This is because during times of crisis our typical forms of reasoning and action may no longer serve us. It is precisely during such times that new ways of thought, action and leadership are needed. A key question for researchers to consider is: Why and how times of crisis serve as an impetus for creative actions and outcomes? The purpose of this paper is to address this question. I open by briefly discussing the features of a crisis. I then introduce an empirically testable, process model that outlines various pathways, factors, and outcomes associated with different ways people and organizations respond during times of crisis. I close by briefly outlining future directions for theory and research.